Electrochemical Remediation of Marine Sediments Spiked With Hg and PAHs: Comparison of the Enhancing Agents’ Nature - Federica Proietto; Claudia Prestigiacomo; Fabio D’Agostino; Maria Bonsignore; Mario Sprovieri; Alessandro Galia; Onofrio Scialdone (International Journal of Chemical Engineering, 2025)
Real marine sediments dredged from Capo Granitola (CG) (Sicily, Italy) artificially contaminated were treated via an electrokinetic (EK) process. Mercury (Hg) and phenanthrene (PHE) or a mixture of PAHs (to simulate a more complex site) were selected as models of heavy metals and organic hazardous compounds, respectively. The aim of this work was to systematically investigate the effect of different enhancing agents on the removal of both classes of contaminants. Marine sediments were treated using a three-compartment cell under 1 V cm−1 for 10 days. The usage of different enhancing agents, including deionized water, trisodium N-(1-carboxylatoethyl)-iminodiacetate hydrate (MGDA) as chelating agents, Tween 80 surfactant and hydrogen peroxide, was investigated, to prompt the simultaneous removal of both classes of contaminants. The optimum option for the simultaneous removal was observed using a MGDA and Tween 80 solution as anolyte and MGDA solution as catholyte. These adopted conditions allow to reach the highest removal of Hg up to 22.5% and of PHE up to 62% in the case of the sediments contaminated with Hg and PHE and a total Hg removal of 13% coupled with a total PAHs removal of 45% in the case of sediments spiked with Hg and a mixture of five PAHs. It was observed that the nature of the enhancing agents used as electrolytes and their combination strongly affect the remediation treatment in terms of both distribution into the sediments and the total contaminants’ removal.